Flutamide versus a cyproterone acetate-ethinyl estradiol combination in moderate acne: a pilot randomized clinical trial - Adalatkhah H; Pourfarzi F; Sadeghi-Bazargani H (Dove Medical Press, 2011)
Hassan Adalatkhah1, Farhad Pourfarzi2, Homayoun Sadeghi-Bazargani31Department of Dermatology, 2Department of Social Medicine, Faculty of Medicine, Ardabil University of Medical Sciences, Ardabil; 3Statistics and Epidemiology Department, Faculty of Health and Nutrition, Tabriz University of Medical Sciences, Tabriz, IranBackground: The use of oral flutamide is rarely investigated in acne therapy. The aim of this study was to compare the efficacy of oral flutamide with that of a cyproterone-estradiol combination in treating acne lesions.Methods: A randomized clinical trial enrolled patients with moderate acne into two equal groups to receive either oral flutamide or the cyproterone-estradiol combination for 6 months. Lesion count, Acne Severity Index, and Global Acne Grading system (GAGS) scores were used to assess improvement in acne lesions. The dichotomous measurement scale for primary endpoint assessment was defined as improvement from moderate to mild acne based on GAGS score. Patient satisfaction and dermal fat were also assessed. Intention to treat and per protocol analyses were done, reporting related effect sizes.Results: Both treatments resulted in substantial improvement in acne lesions. Although flutamide seemed to have higher efficacy, an intention to treat analysis did not find the two treatment protocols to be different. The relative risk in intention to treat analysis was 1.8 (95% confidence interval [CI] 0.89–1.6), and was 1.33 (95% CI 1.03–1.72) for the per protocol analysis. The number needed to treat for flutamide compared with the cyproterone-estradiol combination was 7.7 and 4.2 in the intention to treat and per protocol analyses, respectively.Conclusion: Flutamide appears to be more effective than a cyproterone-estradiol combination in some aspects of acne treatment, but this requires confirmation in a larger trial.Keywords: acne vulgaris, flutamide, cyproterone acetate, ethinyl estradiol, androgen antagonists